Perforated gastric ulcer: An unusual cause of peritonitis in children - Abdelouhab Ammor; Siham Nasri; Maria Rkain; Houssain Benhaddou (Wolters Kluwer Medknow Publications, 2020)
Perforated gastric ulcer is a particularly rare cause of peritonitis in children. Only few cases have been reported in the literature. It is a serious emergency condition which can be overlooked leading to life-threatening consequences. We report a case of a 12-year-old girl who presented with acute abdominal pain and signs of peritonitis. Surgical exploration found a gastric perforation on the anterior side of the antrum. Primary repair of the perforation was performed after thorough decontamination and taking biopsies from its edges. The post-operative period was uneventful. Helicobacter pylori test was negative. Histopathology result was suggestive of ulceration in the gastric wall and did not isolate H. pylori. Gastro-duodenal ulcer perforation should be considered in the differential diagnosis of children presenting with acute abdomen, especially when imaging showing pneumoperitoneum.